THE PROCESS OF STUDY IN THE FIELD OF TRAMS’ MODERNIZATION - Chudzikiewicz, A.; Bogacz, R. (Science and Transport Progress, 2004)
The main purpose of the article is to show the accepted assumptions and the investigation process necessary to modernize the tram of type 805Na. The modernization process is one of the elements of the tram renovation strategy in Poland [1]. One to the complexity of the task the investigation started after the tram to be modernized had been chosen and finished when the modernized tram went into operation. The above mentioned modernization concerns the complete modernization and means the creation of a modern design tram of type 805Na, that meets the current requirements of both the transportation service and passengers.